PENGARUH UMUR DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG DENGAN PROFITABILITAS DAN SOLVABILITAS SEBAGAI VARIABEL MODERATING - Kurnia Rina Ariani; Andy Dwi Bayu Bawono (Universitas Muhammadiyah Surakarta, 2018)
This research aims to analyze the effect of companies ages and size to audit report lag with profitability and solvability as a moderating variable in manufacturing companies listed in Indonesian Stock Exchange for year end from 2015-2016. Moderating variable used in this research to know whether profitability and solvability can moderate the relationship between companies ages and size to audit report lag. Using Moderated Regression Analysis this research can provide empirical evidence that (i) companies ages has no effect on audit report lag, (ii) companies size has negative effect on audit report lag (iii) profitability and solvability cannot moderate the relationship between companies ages and size to audit report lag.